Bone necrosis of the jaws associated with bisphosphonate treatment: a report of twenty-nine cases - Merigo, E.; Manfredi, M.; Meletri, et al., M. (Acta Biomedica Atenei Parmensis, 2006)
Bone necrosis of the jaws is often related to head and neck radiotherapy, to surgical procedures at maxillary or mandibular level but also to various local and systemic factors such as haematological diseases, haemoglobinopathies and systemic lupus eritematosus; its pathogenesis maybe associated with defects of vascularization. Bisphosphonate are synthetic analogues of pyrophosphate used for the treatment of hypercalcemia in patients with malignancies and bone metastasis and for the treatment of many other disorders such as metabolic bone diseases, Paget’s disease, and osteoporosis; their pharmacological activity is related to the inhibition of the osteoclastic function which leads to resorption and reduction of bone vascularization. Since the end of 2003 Bisphosphonate-associated Osteonecrosis (BON) has become an increasing problem and the test of that is the increase of the relative published case report and case series. Here we report 29 cases of bone necrosis of the jaws in patients treated with pamidronate (Aredia), zoledronate (Zometa) and alendronate: 15 underwent surgical procedures and 14 occurred spontaneously. Among these patients (21 females, 8 males; mean age between 45 and 83 years); 14 were treated for bone metastasis, 12 for multiple myeloma and 3 for osteoporosis. Bone necrosis involved only maxilla in 7 patients, only mandible in 20 patients and both in 2 patients. Six patients had multiple osteonecrotic lesions, 3 contemporary lesions and 3 non contemporary. In these patients we performed 3 kinds of therapy, associated or not: medical therapy (with antibiotic drugs, antimycotics and antiseptic mouthwashes), surgical therapy with curettage or sequestrectomy and Nd:YAG laser biostimulation.